Computer Application to Simulate the Flight of a GROM Type Anti-Aircraft Guided Missile - MOTYL, Krzysztof; GĄSIOR, Karol (Problems of Mechatronics Armament Aviation Safety Engineering, 2020)
The paper presents the features of the computer application developed in the RAD Studio XE4-10.1 Berlin programming environment for the simulation of guided flight of the GROM type missile. The application uses an integrated algorithm to solve a system of differential equations, as well as a dynamics model for the missile, target and atmosphere. Further to this, simulation tests have also been conducted.